Abundância das formas imaturas de Psaroniocompsa incrustata ( Lutz, 1910) (Diptera: Simuliidae) em um criadouro natural no rio Pium/RN, e sua fauna associada - Rodrigues, Francilene Miranda dos Santos (2006)
The species psaroniocompsa incrustata (Lutz, 1910) was studied in relation to its abundance in different and seasonal periods, the physico-chemical of the breending ground and the fauna predation added to the immature of the species. The study was developed during eight months, from April to July, 2005 (rainy season) and from October, 2005 to January, 2006 (drought season), in one natural breending ground situated in the Pium river, that is part of the hydrographical basin of the Pirangi river in Rio Grande do Norte. The immature of Simuliidae were collected manually in vegetal substrate. At the same place, it was made one sampling of the associated fauna using Suber collectors and the measurement of the environment variants. It was also made one analysis of the stomach content of possible enemies of the simulídeos, to observe the predation of the associated fauna. It was collected 7.713 samples, all from de species P. Incrustata, it was observed a bigger abundance in the drought season, and the entomologic fauna associated totalizing 20.1314 species, distributed in the kinds: Diptera, Ephemeroptera, Odonata, Trichoptera, e Hemiptera, with a bigger representativity of Dipteros. The analysis of the stomach content of the species from the families Libellulidae and Hydropsychidae showed the presence of the simulídeos in only 4% of the material analysed, therefore it was not confirmed the presence of one efficient biological control of the simulídeos in this breending ground